Crossover from ballistic to Epstein diffusion in the free-molecular regime - Heinson, William R.; Pierce, F.; Sorensen, Christopher M.; Chakrabarti, Amitabha (My University, 2015)
We investigate, through simulation, a system of aggregating particles in the free molecular regime that undergoes a crossover from ballistic to diffusive motion. As the aggregates grow, the aggregate mean free path becomes smaller and the motion between collisions becomes more diffusive. From growth kinetics we find that when the ratio of the aggregate mean path to the mean aggregate nearest neighbor separation reaches of the order of unity, a crossover to diffusive motion occurs. This ratio, called the nearest neighbor Knudsen number, becomes an important parameter in understanding aerosol aggregation in the free molecular regime.
Keywords: Aerosol aggregation; Aerosols